MATH SOLVE

4 months ago

Q:
# How do I do this, please explain

Accepted Solution

A:

Step-by-step explanation:Substitute the numbers or variables you get when you plug in the numbers into the inner function into the outer function.a) Simplify p(u(x)).let's say we get p(u(x)) when we plug u(x) into p(x)1....You can observe that the x inside p(x) got substituted by u(x)We know the equations of p (x) & u (x) from the question.p(x) = x-4/x+1 u(x) = 4x + 2use concept 1. p(u(x)) = 4x+2 - 4 / 4x+2 + 1 ....substituted u(x)'s value into x of p(x).2.......= 4x-2 / 4x+3..b) use the same method i used above. but now we have numbers instead of x to substitute with. use 2.. p(u(2)) = 4(2) - 2 / 4(2)+3 = 8 - 2 / 8 + 3 = 6 / 11.